Post-intubation iatrogenic tracheobronchial injuries: The state of art - Passera, Eliseo; Orlandi, Riccardo; Calderoni, Matteo; Cassina, Enrico Mario; Cioffi, Ugo; Guttadauro, Angelo; Libretti, Lidia; Pirondini, Emanuele; Rimessi, Arianna; Tuoro, Antonio; Raveglia, Federico (Frontiers in Surgery, 2023)
Iatrogenic tracheobronchial injury (ITI) is an infrequent but potentially life-threatening disease, with significant morbidity and mortality rates. Its incidence is presumably underestimated since several cases are underrecognized and underreported. Causes of ITI include endotracheal intubation (EI) or percutaneous tracheostomy (PT). Most frequent clinical manifestations are subcutaneous emphysema, pneumomediastinum and unilateral or bilateral pneumothorax, even if occasionally ITI can occur without significant symptoms. Diagnosis mainly relies on clinical suspicion and CT scan, although flexible bronchoscopy remains the gold standard, allowing to identify location and size of the injury. EI and PT related ITIs more commonly consist of longitudinal tear involving the pars membranacea. Based on the depth of tracheal wall injury, Cardillo and colleagues proposed a morphologic classification of ITIs, attempting to standardize their management. Nevertheless, in literature there are no unambiguous guidelines on the best therapeutic modality: management and its timing remain controversial. Historically, surgical repair was considered the gold standard, mainly in high-grade lesions (IIIa-IIIb), carrying high morbi-mortality rates, but currently the development of promising endoscopic techniques through rigid bronchoscopy and stenting could allow for bridge treatment, delaying surgical approach after improving general conditions of the patient, or even for definitive repair, ensuring lower morbi-mortality rates especially in high-risk surgical candidates. Our perspective review will cover all the above issues, aiming at providing an updated and clear diagnostic-therapeutic pathway protocol, which could be applied in case of unexpected ITI.